2018
DOI: 10.1016/j.ajpath.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclooxygenase-2 Suppresses the Recruitment of Endothelial Progenitor Cells in the Microvasculature of Endometriotic Lesions

Abstract: The incorporation of endothelial progenitor cells (EPCs) into newly developing blood vessels contributes to the vascularization of endometriotic lesions. We analyzed whether cyclooxygenase (COX)-2 signaling regulates this vasculogenic process. Endometriotic lesions were surgically induced in irradiated FVB/N mice, which were reconstituted with bone marrow from FVB/N-TgN [Tie2/green fluorescent protein (GFP)] 287 Sato mice. The animals received β-estradiol 17-valerate once a week and were treated daily with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…This is mirrored in coronary heart disease, reinforcing the connections between ECFC dysfunction, aging, and cardiovascular risk ( 28 ). However, there are also reports that bone-marrow derived progenitor cell numbers remain stable, suggesting that, in some cases, the decline in reparatory ability may be due to cellular impairments, in their homing, angiogenic capacity or their propensity for senescence and premature cell death ( 28 , 30 , 31 ). Studies have shown that late ECFCs from elderly volunteers demonstrate impaired migration, proliferation and adhesion properties compared to those from young participants ( 29 , 32 , 33 ), and show a reduced capacity for re-endothelialization and incorporation into a damaged vasculature ( 29 ).…”
Section: Defective Epcs In Aging and Diabetesmentioning
confidence: 99%
“…This is mirrored in coronary heart disease, reinforcing the connections between ECFC dysfunction, aging, and cardiovascular risk ( 28 ). However, there are also reports that bone-marrow derived progenitor cell numbers remain stable, suggesting that, in some cases, the decline in reparatory ability may be due to cellular impairments, in their homing, angiogenic capacity or their propensity for senescence and premature cell death ( 28 , 30 , 31 ). Studies have shown that late ECFCs from elderly volunteers demonstrate impaired migration, proliferation and adhesion properties compared to those from young participants ( 29 , 32 , 33 ), and show a reduced capacity for re-endothelialization and incorporation into a damaged vasculature ( 29 ).…”
Section: Defective Epcs In Aging and Diabetesmentioning
confidence: 99%
“…This observation can be explained by the fact that the engraftment of the transplanted uterine tissue is already completed at this late time point. Accordingly, this phase of lesion development is rather characterised by vessel maturation and remodelling than by extensive angiogenesis and cell turnover (Rudzitis‐Auth, Nenicu, Nickels, Menger, & Laschke, 2016; Rudzitis‐Auth, Nickels, Menger, & Laschke, 2018). Therefore, we performed additional analyses of peritoneally transplanted uterine tissue on Day 7 and detected a reduced microvessel density and stromal cell proliferation within NVP‐BHG712‐treated lesions when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…For the in vivo experiments, the group sizes were chosen according to previous studies using the herein described endometriosis models (Feng, Menger, & Laschke, 2013; Rudzitis‐Auth, Nenicu, Nickels, Menger, & Laschke, 2016; Rudzitis‐Auth, Nickels, Menger, & Laschke, 2018). Data were first analysed for normal distribution and equal variance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our findings revealed the identity of key prostaglandins activated during early decidualization, potentially offering an opportunity to target these molecules for therapeutic development. Clinically, targeting specific terminal prostaglandin species, may provide a putative non-steroidal solution to alleviate pain and chronic inflammation for certain reproductive disorders, while maintaining or restoring endometrial receptivity (Lee et al , 2013; Laux-Biehlmann et al , 2015; Rudzitis-Auth et al , 2018). Thus, revisiting the role of specific prostaglandins and their receptors that may be critical for reproductive function of both the gravid and non-gravid uterus is appropriate.…”
Section: Discussionmentioning
confidence: 99%